DOES ESG PERFORMANCE MATTER? CEO POWER AND FIRM VALUE IN ASEAN MARKET: - - Cahyawati, Noor Endah; Pandu Wicaksono, Aditya (Akurasi : Jurnal Studi Akuntansi dan Keuangan, 2025)
This study examines the effect of Environmental, Social, and Governance (ESG) performance on firm value and the moderating role of CEO power in ASEAN markets. Drawing on legitimacy theory and stakeholder theory, the research applies a quantitative approach using panel data from 133 public companies across Indonesia, Malaysia, Singapore, Thailand, and the Philippines during 2015-2019. ESG data were obtained from Refinitiv, while CEO power was proxied by tenure extracted from annual reports. The analysis utilizes multiple regression and Two-Stage Least Squares (2SLS) to address endogeneity. Results reveal that environmental and social performance have significant negative effects on firm value (Tobin's Q), while governance performance is not significant. CEO power negatively moderates the environmental performance-firm value relationship, indicating the strategic role of leadership in sustainability policy. Findings suggest that ESG initiatives have not yet been fully reflected in economic value within ASEAN markets. The study emphasizes the importance of top management support and more developed market responses to integrate ESG into sustainable business strategies.